تأثير جودة خدمة التعليم الالكتروني عبر منصة موودل على رضا الطلبة ونية استخدامهم للتعليم الالكتروني في الجزائر، دراسة حالة جامعة سعيدة.: Impact of service quality e-learning via moodle platform on student satisfaction and use intention in Algeria, Case Study University of Saida. - لحسن عطاالله (Journal of North African Economies, 2025)
This research aims to identify the Impact of service quality e-learning on student satisfaction and use intention in Algeria, and in order to research this determinants we distributed an questionnaire to university students the sample size was 147 students, and analyze them by using a partial least squares structural equation, the finding of this research show that there is an positive Impact of service quality e-learning on students satisfaction and use intention, moreover the service quality e-learning positively and indirectly intention to use e-learning through students satisfaction.